Le nouveau bâtiment des archives de l'État à Liège - Hansotte, Georges (Archives et bibliothèques de Belgique (ABB), 1988)

Missions impossibles ? - René-Bazin, Paule; Prax, Hélène (Gazette des archives, 1978)
The relations between the Archives nationales and the Ministries have been entrusted since 1950 to archivists of the Archives nationales with either a permanent or a parttime mission. Since 1967, these relations are also entrusted to the Cité des Archives contemporaines (Intermediate repository) of Fontainebleau. Archivists in charge of the missions describe the organisation of their work and propose some regulatory and technical improvements.

Le déménagement des Archives départementales de l'Aisne - Souchon, Cécile (Gazette des archives, 1978)

Manuel d'archivistique. Théorie et pratique des Archives publiques en France - Association des archivistes français (AAF) (1970)